Jarosite occurrence in the Deccan Volcanic Province of Kachchh, western India: Spectroscopic studies on a Martian analog locality. Issue 3 (24th March 2016) - Bhattacharya, Satadru; Mitra, Souvik; Gupta, Saibal; Jain, Nirmala; Chauhan, Prakash; Parthasarathy, G.; Ajai,
Abstract: The sulfate mineral jarosite is considered a key indicator of hydrous, acidic, and oxidizing conditions on the surface of early Mars. Here we report an analog terrestrial locality hosting jarosite from Matanumadh, Kachchh, western India, using detailed spectroscopic studies on weathered basalts of the Deccan Volcanic Province and overlying tuffaceous shales and sandstones of the Matanumadh Formation. Hyperspectral data in the visible/near‐infrared (350–2500 nm) to midinfrared (4000–400 cm −1 ) region of the electromagnetic spectrum and X‐ray diffraction patterns have been acquired on samples collected from the field to detect and characterize the hydrous sulfate and phyllosilicate phases present at the studied site. Hydrous sulfates occur in association with Al‐rich phyllosilicates (kaolinite) that overlie a zone of Fe/Mg smectites in altered basalts. Jarosite is found within both saprolitic clay horizons altered from the basalt and within variegated sandstone and shale/clay units overlying the saprolite; it mostly occurs as secondary veins with or without gypsum. Jarosite is also seen as coatings on kaolinite clasts of varying shapes and sizes within the tuffaceous variegated sandstone unit. We argue that the overall geological setting of the Matanumadh area, with this unusual mineral assemblage developing within altered basalts and in the overlying sedimentary sequence, mimics the geological environment of many of the identified jarosite localities on Mars and can be considered as a Martian analog from this perspective. Key Points: We report an analog terrestrial locality hosting jarosite from Matanumadh, Kachchh VNIR and mid‐IR spectroscopy of jarosite samples has been carried out The coexistence of jarosite with other sulfates in the Matanumadh Formation suggests an environment similar to jarosite localities on Mars